Vida fluída e escrita perversa : a questão identitária em A Céu aberto de João Gilberto Noll - Hartmann, Giuliano (2011)
The present thesis aims to promote a view on the identity issues in "A céu aberto" (1993), a João Gilberto Noll's novel, covered by two perspectives: on the one hand, anchored by the fluidity proposed by Zigmunt Bauman, which indicates the global order that, by dismissing borders, launches the subjects to the drift; and, on the other hand, under the aegis of Slavoj Zizek's political philosophy which with opposing theories pushes subjects towards annihilation, it attempts to rescue the lost subjectivity before the ideological simulacrum from the contemporary society. It is understood that the nollian narrative questions identity and its developments, either on the sociological, philosophical sphere, as well as particularly regarding the romance function as a society representation which is built upon thin and controversial pillars of the huge modernity project.